DEVELOPMENT OF LEARNING MULTIMEDIA TO MAKE DIGITAL TUNIC PATTERNS BASED ON SAC (SMART APP CREATOR) FOR VOCATIONAL HIGH SCHOOL STUDENTS - Aisah, Meita Yustika; Sugiyem, Sugiyem (Universitas Labuhanbatu, 2025)
Purpose – This research aims to (1) Develop multimedia learning for making digital tunic patterns based on SAC (Smart App Creator) and (2) Determine the feasibility of learning multimedia for making digital tunic patterns based on SAC (Smart App Creator).Methodology—This research is R&D (Research & Development) development research using the ADDIE development model. The media developed before being tested on users is first validated by media and material experts. The test subjects for this research were 20 students and 19 teachers who were digital pattern-making training participants. The data analysis technique used is quantitative descriptive analysis.Findings – The results of the research show that: (1) multimedia learners in making digital tunic patterns based on SAC were developed in the form of an Android application and WEB with specifications a) Application size 98MB, b) portrait screen display c) screen resolution 1080 x1920 pixels d ) Android system Lollipop 5.0 and later; The results of the research show that: (1) multimedia learners in making digital tunic patterns based on SAC were developed in the form of an Android application which can also be accessed via WEB with specifications a) Application size 98MB, b) portrait screen display c) screen resolution 1080 x1920 pixels d ) Android system Lollipop 5.0 and later ; (2) the feasibility of the material aspect obtained a percentage of 94% in the